2003
DOI: 10.1038/sj.bjc.6601125
|View full text |Cite
|
Sign up to set email alerts
|

Ligands of the peripheral benzodiazepine receptor induce apoptosis and cell cycle arrest in oesophageal cancer cells: involvement of the p38MAPK signalling pathway

Abstract: Specific ligands of the peripheral benzodiazepine receptor (PBR) are known to induce apoptosis and cell cycle arrest in oesophageal cancer cells. However, the underlying mechanisms are still unknown. Here, we investigated the transcriptional alterations and activation of protein kinases in response to PBR-specific ligands. Using cDNA arrays, we examined the transcriptional effects of the PBR-specific ligand FGIN-1-27 in two oesophageal cancer cell lines, KYSE-140 (squamous cell carcinoma) and OE-33 (adenocarci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 52 publications
2
40
0
Order By: Relevance
“…However, PBR as a critical part of the mitochondrial permeability transition pore (mPT) has been shown to mediate enhancing the apoptosis. [9][10][11][12][13][14] In a previous study by the current authors, 21) anticancer cytotoxic flavonoids including apigenin elicited up-regulation of PBR mRNA expression in SK-N-Mc human neuroblastoma cells. Moreover, in this study, treatment with PBR ligands consistently inhibited the SNU-C4 cell survival, and diazepam also produced anticancer cytotoxic effects, similar to those caused by flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…However, PBR as a critical part of the mitochondrial permeability transition pore (mPT) has been shown to mediate enhancing the apoptosis. [9][10][11][12][13][14] In a previous study by the current authors, 21) anticancer cytotoxic flavonoids including apigenin elicited up-regulation of PBR mRNA expression in SK-N-Mc human neuroblastoma cells. Moreover, in this study, treatment with PBR ligands consistently inhibited the SNU-C4 cell survival, and diazepam also produced anticancer cytotoxic effects, similar to those caused by flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…5D). However in these cells, the has already been questioned in several studies where the concentration range needed to achieve a toxic effect was always two or three orders of magnitude higher than the affinity of PBR ligands for their receptor [8][9][10][11][12]. Furthermore, a similar debate existed about the effect of PBR ligands on cell proliferation [43], and it has just been demonstrated that such a property was independent of their ability to bind PBR [44].…”
Section: Ro 5-4864-induced Cell Death Is Associated With a Mitochondrmentioning
confidence: 99%
“…The present study, viewed in the context of our previously reported data, suggests that the p38 pathway promotes G 2 arrest via Gadd45␣ induction in response to hyperosmolality. Gadd45␣ induction also depends on p38 activity in human neuroblastoma cells exposed to oxidative stress (45), human epithelial cells exposed to flavonoids (46), and esophageal cancer cells exposed to peripheral benzodiazepine receptor-specific ligands (47). Conversely, p38 activity depends on MEKK4 activation mediated by each of the three Gadd45 proteins in response to a diverse array of stimuli (5,26,48,49).…”
Section: Gadd45␣⁄␤ and Gadd45␥mentioning
confidence: 99%